Dasar tidak campurtangan ASEAN - Ramli Dollah; Wan Shawaluddin Wan Hassan (University of Malaya, 2009)
Since its inception in August 1967, the Association of Southeast Asians (ASEAN) has been firm in maintaining its policy of non-interference, The policy has been re-emphasized in 1976 with signing of the Treaty of Amity and Cooperation (TAC). Although the policy managed to hold ASEAN's unity, the Asian financial crisis has challenged the very unity and non-interference policy of ASEAN. This article analyzes why ASEAN should hold its stance in maintaining a non-interference policy, which has been the main pillar since the 1960s. Despite mounting pressure from the West and intense challenges from its surrounding environment, including globalization, economic crisis and the rise of violence and human rights abuses, ASEAN's continued its efforts to uphold the policy in order to ensure its relevancy in the most challenging world.